а) 3x+2x=10

б) 5x+x=6

в) 4x+2x-7=5

г) 7x+x+3=19

д) 5=x4x-3x

е) 8=3x-x

ж) 3x-1=2x

з) 3x-6=x

и) x+3=3x-7

к) 7x+2=3x-10

л) 1/2x-3=2-1/3x

м) 2/5x-1=3/4x-6

н) 2x-6=0

о) -x+7=0

п) 3x+1=7

р) 5x-2=1

с) 2(x-5)=9

т) -(x+8)=3

у) 7-3(x+1)=6

ф) 2x-(7+x)=2

х) 12+3(x-1)=0

ц) 1-5(2-3x)=6

ч) 5-2(3-x)=11

ш) -3-3(3-2x)=1

2

Ответы и объяснения

2013-01-25T15:53:50+00:00

а) 3x+2x=10

5х=10

х=10/5=2

б) 5x+x=6

6х=6

х=6/6=1

в) 4x+2x-7=5

6х=5+7=12

х=12/6=2

г) 7x+x+3=19

8х=19-3=16

х=16/8=2

д) 5=4x-3x

х=5

е) 8=3x-x

2х=8

х=8/2=4

ж) 3x-1=2x

3х-2х=1

х=1

з) 3x-6=x

3х-х=6

2х=6

х=6/2=3

и) x+3=3x-7

3х-х=3+7=10

2х=10

х=10/2=5

к) 7x+2=3x-10

4х=-12

х=-12/4=-3

л) 1/2x-3=2-1/3x

1/2х+1/3х=2+3=5

3х+2х=30

5х=30

х=30/5=6

м) 2/5x-1=3/4x-6

2/5х-3/4х=1-6=-5

8х-15х=-100

х=7/100

н) 2x-6=0

2х=6

х=6/2=3 

о) -x+7=0

х=7

п) 3x+1=7

3х=6

х=6/3=2

р) 5x-2=1

5х=3

х=3/5

с) 2(x-5)=9

2х=19

х=19/2=9,5

т) -(x+8)=3

-х=3+8=11

х=-11

у) 7-3(x+1)=6

-3х=6+3-7=2

х=-2/3

ф) 2x-(7+x)=2

2х-х=2+7=9

х=9

х) 12+3(x-1)=0

3х=-9

х=-9/3=-3

ц) 1-5(2-3x)=6

15х=6-1+10=15

х=1

ч) 5-2(3-x)=11

2х=11-5+6=12

х=12/2=6

ш) -3-3(3-2x)=1 

6х=1+3+9=13

х=13/6=2 1/6

2013-01-25T16:15:10+00:00

а) 3х+2х=10        5х=10          х=2

б)5х+х=6        6х=6      х=1

в) 4х+2х=7+5         6х=12       х=2

г) 7х+х=19-3         8х=16        х=2

д) напиши еще раз

е) 3х-х=8         2х=8      х=4

ж)3х-1=2х   3х-2х=1         х=1

з)3х-6=х       3х-х=6        2х=6     х=3

и)х+3=3х-7           х-3х=-7-3            -2х=-10           -х=-5      х=5

к)7х+2=3х-10        7х-3х=-10-2      4х=-12        х=-3

л)1/2х+1/3х=2+3   5/6х=5       х=6

м) 2/5х-3/4х=-6+1                           -7/20х=-5       х=7/4

н)2х-6=0       2х=6      х=3

о)-х=-7    х=7

п)3х=7-1     3х=6     х=2

р)5х=3      х=3/5

с)2х-10=9       2х=19      х=9,5

т)-х-8=3        -х=-5     х=5

у)7-3х-1=6       -3х=0         х=0

ф)2х-7-х=2         х=9

х) 12+3х-3=0       3х=-9       х=-3

ц)1-10-15х=6         15х=15    х=1

ч)5-6+2х=11    2х=12     х=6

ш)-3-9+6х=1      6х=13    х=2,5